THE STUDY OF JELAWAT FISH SAUSAGE FORMULATION (Leptobarbus hoeveni) BY USING DIFFERENT DOSE OF TAPIOCA FLOUR ON CONSUMER ACCEPTANCE - Napsarina '; Suparmi '; Dewita ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The purpose of this research was to determine the formulation of jelawat fish sausage (Leptobarbus hoeveni) by using different dose of tapioca flour on consumer acceptance. The method used in this research was experimental method with completely randomized design (CRD) non factorial by given different dose of tapioca flour (treatment), S0 (without tapioca flour), S1 (5% tapioca flour), S2 (10% tapioca flour), S3 (15% tapioca flour). Based on consumer acceptance, it can be concluded that jelawat fish sausage by using 5% tapioca flour more preferable by consumer acceptance, with criterias (3,36) odor (3,30) texture (3,40)and taste (3,30). Furthermore, the proximate value was water content(66.03%), protein content(13.68%), fat content (12.35%), ash content (2.64%) and carbohydrate content (5.30%).Kata Kunci : sausage, fish jelawat, tapioca flour, consumer acceptance